Renal Cell Carcinoma Associated With HIV/AIDS: A Review of the Epidemiology, Risk Factors, Diagnosis, and Treatment - Zhu, Zhiqiang; Zhang, Yihang; Wang, Hu; Jiang, Taiyi; Zhang, Mengmeng; Zhang, Yu; Su, Bin; Tian, Ye (Frontiers in Oncology, 2022)
Renal cell carcinoma (RCC), one of the most common genitourinary tumors, is induced by many factors, primarily smoking, obesity, and hypertension. As a non-acquired immunodeficiency syndrome (AIDS)-defining cancer, human immunodeficiency virus (HIV) may also play a critical role in the incidence and progression of RCC. It is evident that individuals who are infected with HIV are more likely than the general population to develop RCC. The age of RCC diagnosis among HIV-positive patients is younger than among HIV-negative individuals. However, many other characteristics remain unknown. With the increase in RCC incidence among HIV-infected patients, more research is being conducted to discover the relationship between RCC and HIV, especially with regard to HIV-induced immunodeficiency, diagnosis, and treatment. Unexpectedly, the majority of the literature suggests that there is no relationship between RCC and HIV-induced immunodeficiency. Nonetheless, differences in pathology, symptoms, or treatment in HIV-positive patients diagnosed with RCC is a focus. In this review, we summarize the association of RCC with HIV in terms of epidemiology, risk factors, diagnosis, and treatment.